Effect of type 2 diabetes mellitus duration on fasting plasma glucose, serum creatinine, and urinary microalbumin in type 2 diabetics attending to diabetic centre at teaching hospital jaffna - Ruwanpathirana, R.P.E.; Kandeepan, K.; Arasaratnam, V. (University of Jaffna, 2018)
Diabetes Mellitus is the most common non communicable chronic metabolic disease worldwide. Renal complications are one of the major complications apart from cardiovascular, neurological and retinal complications. The objective of this study was to evaluate the effect of type 2 diabetes mellitus duration on fasting plasma glucose, serum creatinine and urinary microalbumin in type 2 diabetics attending to Diabetic Centre at Teaching Hospital Jaffna. A total of 98 patients diagnosed as type 2 diabetics without chronic kidney diseases were included. Fasting plasma glucose (Glucose Oxidase method), serum and urine creatinine (Jaffe Alkaline Picric Acid method) and random urine albumin (Immunoturbidimetry method) were estimated. The strength of correlation was determined by Pearson correlation. The mean (±SD) fasting plasma glucose, serum creatinine and urine albumin to creatinine ratio were 136.17 (±53.92) mg/dL, 1.25 (±0.64) mg/dL and 49.31 (±102.64) mg/g creatinine respectively. The mean (±SD) random urine creatinine, random urine albumin and duration of diabetes mellitus were 1.21 (±0.80) g/L, 34.38 (±54.04) mg/L and 9.28 (±7.20) years respectively. Out of 98 type 2 diabetics, 69 (70.41%), 25 (25.51%), and 4 (4.08%) had normoalbuminuria, microalbuminuria and macroalbuminuria respectively. When the duration of diabetes mellitus was increased, fasting plasma glucose level, serum creatinine, random urine albumin and urine albumin to creatinine ratio were gradually increased. But random urine creatinine was gradually decreased with the duration of diabetes mellitus. The longest duration of diabetes mellitus was 13.57 (±9.93) years in the sub group of ≥201 mg/dL. The highest urine albumin to creatinine ratio ≥61 mg/g was resulted in the mean (±SD) duration of diabetes mellitus 14.27 (±7.70) years which was the longest duration of diabetes mellitus. On applying Pearson correlation, duration of diabetes mellitus showed a weak positive correlations with fasting plasma glucose (r = 0.251, p = 0.013) and serum creatinine (r = 0.097, p = 0.340). Urine albumin to creatinine ratio showed a weak positive correlation with duration of diabetes mellitus which was statistically significant (r= 0.430, p= 0.000). This study revealed that FPG, serum creatinine and albumin excretion were increased with the duration of diabetes mellitus in type 2 diabetics.
Keywords: Creatinine; Duration of diabetes; Microalbuminuria; Plasma glucose